Quantitative Measurement of Innovation Ecosystems: Example Portugal - Wehrspohn, R.B.; Salavisa, I.; Ribeiro, B.; Machado, J.F.; Zadražil, M.; Di Noto, V.; Zschech, E. (Policy Papers on Just Transition No. 06, 2025)
The design of efficient and effective innovation ecosystems is crucial to every society, in particular to address structural changes via innovations. We developed a four-quadrant model to map the established research and innovation landscape with the coordinates Excellence in Science and Excellence in Tech Transfer. The model distinguished between fundamental research, applied research and industrial testing labs. We tested successfully our model in the Portuguese Research & Development (R&D) system by comparison with qualitative interviews.